Will I Get Paid? Employee Stock Options and Mergers and Acquisitions - Babenko, Ilona; Du, Fangfang; Tserlukevich, Yuri (Journal of Financial and Quantitative Analysis, 2021)
We analyze how employee compensation contracts of target firms affect merger terms and outcomes. Using unique data from merger agreements, we document that in 80.0% of all merger and acquisition (M&A) deals, at least some of the target’s employee stock options (ESOs) are canceled by the acquirer and not replaced by new equity-based grants. Contract modifications reduce the value of ESOs by 38.4% in the average M&A deal. Further, the combined merger returns are larger when employees experience greater losses. Overall, our results indicate that the benefits of reducing the number of ESOs outweigh the potential negative effects on firm value.